Konsep Kesetaraan Gender dalam Pendidikan Islam - Kartika, Nita (Tsamratul Fikri | Jurnal Studi Islam, 2020)
Islam is a religion that upholds the value of justice and equality contains the principles of equality. Men and women alike as creatures of Allah, as caliphs on earth and have the potential to achieve optimal potential. Gender Equality is the main agenda of the feminism movement, since the inclusion of gender discourse in Islamic religion, some Muslim thinkers are influenced by the concept of gender, they assume that Islam that came during the time of the prophet has similarities with the concept of gender brought by feminism, finally many texts the laws and verses that have governed the relationship between men and women are reviewed to suit the perspective of gender equality. The problem is many concepts that are not in line even contrary to the concept of justice in Islam. For this reason, the concept of gender equality in Islamic religious education must be known so that there is no gender bias in education. The right of women to obtain education and achieve the same achievements as men is one of the goals of gender equality in education, but the limits taught in Islamic education also need to be considered.